Lipidomic Composition of Lewis Lung Carcinoma Metastases from Mice Fed an Obesogenic, High-fat Diet (P08-126-19). (24th October 2019) - Yan, Lin; Sundaram, Sneha; Bukowski, Michael; Mehus, Aaron; Picklo, Matthew
Abstract: Objectives: Metastasis is a hallmark of cancer. Diet-induced obesity enhances lung metastasis from the primary tumor of Lewis lung carcinoma (LLC) in mice and the lipidomic profile of LLC primary tumor reflects the fatty acid composition of the diet. The objective of this study was to evaluate the impact of feeding an obesogenic, high-fat diet (HFD) on the lipidomic composition of resulting LLC metastases in mice. Methods: Lung metastases were obtained from LLC primary tumor-bearing mice fed the AIN93G diet or a HFD providing 16% or 45% of energy from soybean oil. Triacylglycerols (TAG) in the metastases were analyzed by using a mass spectrometry method wherein the ion source was calibrated with an equimolar TAG standard. Neutral mass losses were used to determine the relative content of selected fatty acids across Brutto structures. Lipidomic data were analyzed by using MetaboAnalyst software (Version 4.0) with a false discovery rate of 0.05. Results: Analysis of TAG composition in metastases identified 51 separate TAGs by Brutto structure. Six TAGs were significantly different between the two diet groups. Concentrations of TAGs containing 48 and 50 acyl carbons were lower and those containing 54 acyl carbons were higher in the HFD-fed mice. In mice fed the HFD, TAG 54:6 was higher whereas TAGs 48:1 and 50:1 were lower in the metastases than in mice-fed the AIN93G diet. The volcano plot analysis of TAGs showed that differences in 3 TAGs between the two groups were at least two-fold. In neutral loss analysis, the acyl chain C and saturation values of 36:4 and 36:5 corresponding to 18:2_18:2 and 18:2_18:3, respectively, were significantly higher in the HFD group than in the AIN93G group. Increases in these linoleic and linolenic acid-containing species reflected the higher concentrations of these fatty acids in the HFD. Conclusions: The lipidomic profile of LLC metastases reflects the fatty acid composition of the diet. It suggests that lipidomic alteration of the metastases by an obesogenic diet may contribute to the aggressiveness of metastatic growth in the lungs. Funding Sources: USDA ARS 3062-51000-050-00D.